Effect of heat treatment on fatigue crack initiation of laser powder bed fusion stainless steel 316L - Zhang, Meng (2018)
Laser powder bed fusion (L-PBF) is an emerging additive manufacturing technique for building structural components. L-PBF processing defects, such as lack of fusion pores, promote fatigue crack initiation and shorten the fatigue life. With well-controlled processing, critical pores can be avoided such that the microstructure-driven intergranular crack initiation mode becomes operative. In this work, the fatigue crack initiation behaviours of as-built and solution annealed L-PBF stainless steel 316L were studied. Crack initiation of the as-built samples is driven by de-bonding of the dendritic grain boundaries. High temperature annealing results in the formation of thermally-induced defects, possibly via the reheat cracking mechanism and the nucleation of pre-existing gas pores. As heat treating could have led to recrystallization and annihilation of the original grain boundary defects, the thermally-induced defects became the new sites for crack initiation. In addition, heat treatment incurred significant reduction in yield strength, such that the interaction of fatigue and ratcheting strain accumulation dominated the deformation behaviour of the material. The resulting fatigue strength in the finite life regime was reduced by about 13% but the fatigue endurance limit was not affected.